2010
DOI: 10.1021/la102312w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Superhydrophobicity on the Barrier Properties of Polymethylene Films

Abstract: Superhydrophobic polymethylene (PM) films provide remarkable protection against the transport of aqueous redox probes as a result of entrapped air at the water/polymer interface. The wetting properties and the topography for a set of superhydrophobic (SH) and nonsuperhydrophobic (NSH) PM films were established to compare their interfacial behavior using electrochemical impedance spectroscopy (EIS). EIS results show that SH PM films exhibit resistances against ion transfer that are approximately 3 orders of mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 58 publications
0
36
0
Order By: Relevance
“…R and C denote the resistance and capacitance, respectively. The EIS feature in characterizing the resistance of current flow between the liquid and solid phases has been implemented to study the wetting behavior of textured and porous surfaces ( Figure ) . When the electrolyte solution penetrates the air‐filled pores, the air gap in the pores and the effective solid–liquid separation distance decreases.…”
Section: Definition Of Surface Wettability: Beyond General Classificamentioning
confidence: 99%
“…R and C denote the resistance and capacitance, respectively. The EIS feature in characterizing the resistance of current flow between the liquid and solid phases has been implemented to study the wetting behavior of textured and porous surfaces ( Figure ) . When the electrolyte solution penetrates the air‐filled pores, the air gap in the pores and the effective solid–liquid separation distance decreases.…”
Section: Definition Of Surface Wettability: Beyond General Classificamentioning
confidence: 99%
“…A series of superwetting materials along with polymer based filtration membranes were employed for the treatment of oily wastewater, driven by external pressure 22 23 24 25 26 . But the most serious limitation of these types of membranes is the low flux and quick decline of permeation due to oil adsorption and/or pore plugging by the oil droplets, which lead to severe fouling and difficulty in cleaning 13 27 28 29 30 . In addition, their poor thermal stability makes them less applicable to high temperature applications.…”
mentioning
confidence: 99%
“…101 Tuberquia et al reported the analysis of polymer films wettability using electrochemical impedance spectroscopy and established a mechanism for wetting transition. 125,126 They highlighted three main steps that lead to Cassie-Wenzel transition: (i) a 'nucleation' step, where small areas beneath air-liquid interface adopt the Wenzel state and get wetted, (ii) a 'propagation' step in which the Wenzel state becomes more dominant and larger air volumes are being displaced, and (iii) a 'termination' step where the air layer is compacted into small isolated air pockets which are located randomly on the surface, with no effective retention ability. 125 The technique represents a powerful tool for real-time wetting characterisation.…”
Section: Electrochemical-based Methodsmentioning
confidence: 99%